Application of video education combined with guidance demonstration in post-operative functional exercise of patients undergoing total hip replacement (视频宣教结合示范指导在人工全髋关节置换术后患者功能锻炼中的应用) - PANG Ni (庞妮); YAO Ting (姚婷) (Journal of International Translational Medicine Limited, 2021)
Objective To investigate the effect of video education combined with guidance demonstration in post-operative functional exercise of patients undergoing total hip replacement. Methods Totally 100 patients undergoing total hip replacement were randomly divided into the study group and control group, with 50 cases in each group. All patients received routine education of post-operative functional exercise, and those in the study group received video education combined with guidance demonstration of functional exercise. The mastery of knowledge about functional exercise, accuracy of exercise, post-operative rehabilitation, post-operative complications and patient satisfaction with nursing service were assessed and compared between two groups. Results A higher degree of mastering knowledge about functional exercise, higher rate of accuracy of exercise and better outcomes of post-operative rehabilitation were observed in the study group than that in the control group, respectively (P＜0. 05). The patient satisfaction degree in the study group was higher than that in the control group (P＜0. 05). Conclusion The video education combined with guidance demonstration is effective to improve the patient mastery of knowledge and practice of post-operative functional exercise, improve the accuracy of exercise, improve the post-operative rehabilitation and patient satisfaction with nursing service. (目的 探讨视频宣教结合示范指导在人工全髋关节置换术后患者功能锻炼中的效果。方法 选取100例行人工全髋关节置换术的患者为研究对象, 按照随机数字法分为试验组和对照组, 各50例。对照组采用常规健康教育, 试验组在常规健康教育基础上增加髋关节功能锻炼视频宣教和责任护士一对一指导。比较两组患者对功能锻炼掌握与运用情况、功能锻炼动作正确率、术后恢复情况、术后并发症发生情况以及对护理工作的满意度。结果 试验组患者对全髋关节功能锻炼掌握与运用情况、功能锻炼动作正确率、术后恢复情况均优于对照组, 差异有统计学意义(P＜0. 05)。试验组患者对护理工作满意度高于对照组, 差异有统计学意义(P＜0. 05)。结论 视频宣教结合准确的示范指导可提高人工全髋关节置换术后患者的髋关节功能锻炼掌握与运用, 提高功能锻炼行为的正确率, 促进患者术后恢复, 提高患者对护理工作满意度。)